Adolescents’ use of music for pain management - Lepping, Rebecca J.; Black, Lora L.; Kline, Kymberly A.; Hanson-Abromeit, Deanna; Chadwick, Andrea L.; Wallace, Dustin P.; Black, William R. (Frontiers in Human Neuroscience, 2025)
To investigate the experiences of adolescents with chronic pain who participated in an intensive interdisciplinary pain treatment program, this secondary study analyzes the themes that emerged regarding the spontaneous utilization of music in coping strategies for chronic pain. During research interviews focused on coping skills and treatment engagement, participants spontaneously reported using music as an effective coping strategy for managing pain. A deductive thematic analysis revealed key themes related to their usage, including using music as a distractor, motivator and in other ways as coping strategies. Since participants indicated that music is essential to their experiences of coping with pain, incorporating these strategies could improve the effectiveness of treatment protocols. To this end, further investigation is necessary to assess the impact of music on adolescents with chronic pain, focusing on its role in enhancing interdisciplinary treatment.